2006
DOI: 10.1063/1.2171002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a barrier oxidation dependence on the interfacial magnetism in Co/alumina based magnetic tunnel junctions

Abstract: Soft x-ray absorption spectroscopy and magnetic circular dichroism at the Co L 2,3 edge have been applied to explore the near-interfacial magnetism of Co electrodes in Co/alumina based magnetic tunnel junctions. By taking into account the formation of CoO at the ferromagnetic ͑FM͒/barrier interface, the change in the total magnetic moment on metallic Co atoms as a function of barrier oxidation has been determined. The results demonstrate a strong correlation between the Co moments and measured TMR values, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Besides techniques dedicated to magnetic and transport measurements, 15 those commonly used are cross-sectional high resolution electron microscopy, 16 in situ differential ellipsometry measurements coupled to xray photoelectron spectroscopy (XPS), 17 ac impedance, 18 photoconductance, 19 soft x-ray absorption. 20 All these techniques have some of the following drawbacks: (1) study limited at the top layers, buried layers are not investigated, (2) necessity of high vacuum environment, (3) induced destruction of the sample, (4) difficulty to reach a sub-nanometric resolution for very thin layers (some angstroms), and (5) determination of the thicknesses of the layers but without additional pertinent structural parameters, as the roughness or the film density.…”
Section: Introductionmentioning
confidence: 99%
“…Besides techniques dedicated to magnetic and transport measurements, 15 those commonly used are cross-sectional high resolution electron microscopy, 16 in situ differential ellipsometry measurements coupled to xray photoelectron spectroscopy (XPS), 17 ac impedance, 18 photoconductance, 19 soft x-ray absorption. 20 All these techniques have some of the following drawbacks: (1) study limited at the top layers, buried layers are not investigated, (2) necessity of high vacuum environment, (3) induced destruction of the sample, (4) difficulty to reach a sub-nanometric resolution for very thin layers (some angstroms), and (5) determination of the thicknesses of the layers but without additional pertinent structural parameters, as the roughness or the film density.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, one can expect a strong enhancement of PMA due to the presence of Co-O bondings at the interface. X-ray studies achieved by Telling et al [12,13] on Co=AlO x =Co MTJs showed that a maximum of Co magnetic moment, corresponding to a maximum in TMR, can be reached by optimally oxidizing the tunnel barrier. Designing high TMR-MTJ using oxygen-induced PMA [6] requires a deep understanding of this phenomenon.…”
mentioning
confidence: 98%
“…With regard to increased moment due to interfacial oxidation, there are some [282] who argue that such induced moment is absent based on empirical data. Recently, experimental [267,283,284] and theoretical work [237,285,286] has shown that there is an optimum level of interfacial oxidation where TMR reaches a maximum. Such work has been completed for Co/Al 2 O 3 and Fe/MgO interfaces, where each system provides similar results, despite rather disparate physical ordering, i.e.…”
Section: Interfaces With Oxides: Oxidation/reduction Reactivitymentioning
confidence: 99%